Multi-project management in inter-organizational contexts. Issue 7 (October 2022) - Martinsuo, Miia; Ahola, Tuomas
Highlights: Project-based firms conduct multiple projects in parallel and in sequence. Inter-organizational contexts cause new requirements to multi-project management. Stakeholder and agency theories explain project-based firms' contexts. Propositions are offered on strategy, resources, governance, and learning. Abstract: Multi-project management is typically considered an intra-organizational endeavor of implementing strategies through programs, portfolios, or lineages of change and development projects. Inter-organizational multi-project management takes place between project-based firms and other actors in project networks. The multi-project aspects in inter-organizational contexts cause significant management complexity, but their specific requirements are inadequately understood. This article explores the nature and requirements of project-based firms' multi-project management in inter-organizational contexts. Parallel and sequential inter-organizational multi-project settings are proposed as an expansion to the dominant intra-organizational research. A thematic framework is developed based on stakeholder and agency theories and previous knowledge from portfolio and program management research complemented with an inductive analysis of extant literature. Consequently, we map and report previous research on multi-project management requirements relevant to inter-organizational contexts concerning strategy, resources, governance, and learning. Propositions are developed and future research is recommended in these domains.